Hubungan Terpaan Berita Iklan Tokopedia BTS dan Terpaan Word of Mouth dengan Minat Menggunakan Aplikasi Tokopedia - Rhola Bachtiar Raharjo; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
This study aims to determine the relationship of each variable, exposure to Tokopedia BTS advertising news (X1), word of mouth exposure (X2) with interest in using the Tokopedia (Y) application. This research uses quantitative research methods. The data collection technique used non probability sampling with a sample size of 50 respondents. The analysis used to test the hypothesis is the Pearson correlation test. Hypothesis testing that has been carried out shows that Tokopedia BTS advertising news exposure with interest in using the Tokopedia application is 0.012 (<0.05) with a correlation coefficient of 0.354, so there is a positive relationship between news exposure and interest in using Tokopedia. The significance result of word of mouth exposure with interest in using is 0.019 (<0.05) with a correlation coefficient of 0.330, so there is a positive relationship between word of mouth exposure and interest in using the Tokopedia application.